BISNIS KELUARGA MANGKUNEGARAN - Muhammad Iqbal Birsyada; Wasino Wasino; Suyahmo Suyahmo; Hermanu Joebagio (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
The history of economic development of Javanese community has experienced a very unique dynamic. In the XV and XVI centuries, trading tradition has been done by Javanese community along the north coastal of Java. But, the trading tradition getting dimmer in line with the strategy of economic centralization carried out by Sultan Agung prohibiting the people to trade in foreign countries. In the XIX century, that’s econdition is change, Mangkunegara IV restore the entrepreneurial tradition through various strategies. In addition, to restoring the entrepreneurial tradition of Javanese society, Mangkunegara IV also broke the old tradition of kepriyayinan (Javanese aristocrate) to want to do business, not just live in pleasure as breeds nobility or gentry class. Therefore, reviewing to the business strategy of Mangkunegaran IV becomes important, as part of the history of economic development Javanese community. By using the historical method and a multidimensional approach, through a variety of primary sources such as Mangkunegara IV literature, the study found that the Mangkunegaran IV’s business strategy conducted by building a centers of sugar cane farm and modernization of sugar factories on a large scale, so as to obtain additional revenue for the Mangkunegaran IV family. The successfull of his business, demonstrates to the Javanese nobility that he was a king who had a strong entrepreneurial spirit.